Leg asymmetries during running in Australian rules football players with previous hamstring injuries - Cronin, J. (The Journal of Strength and Conditioning Research, 2010)
Asymmetries between lower body limbs during athletic movements are thought to increase the risk of injury and compromise performance. Very little is known about the magnitude of leg asymmetries during human running, especially after an acute hamstring injury. The purpose of this study was to quantify the magnitude of leg asymmetries in a number of mechanical variables during running in non-injured and previously injured Australian Rules football (ARF) players. A group of non-injured ARF players (n = 11) and a group of previously injured ARF players (n = 11; hamstring injuries in previous two years) were compared. The legs of the non-injured players were classified as dominant and non-dominant whereas the legs of the injured players were classified as injured or non-injured. The players ran on a non-motorized force treadmill at approximately 80% of their maximum velocity. Kinetic and kinematic data was collected from 12 consecutive steps. For the non-injured players, there were no significant differences between dominant and non-dominant legs for any of the variables - horizontal and vertical force production, vertical stiffness, leg stiffness, contact times, impulse, resonance frequency, positive work and vertical centre of mass displacement. For the injured players, the only variable that was significantly (p < 0.001) different between the injured and non-injured leg was horizontal force production (175 +/- 30 vs. 326 +/- 44 N). Furthermore, the injured leg (injured group) produced significantly less horizontal force than either legs (dominant and non-dominant legs) of the non-injured group (p < 0.05), and the non-injured leg produced significantly more horizontal force than either legs of the non-injured group (p < 0.05). In the present study, hamstring injures have an influence on leg asymmetries in horizontal but not vertical force production during running at sub-maximal velocities. Furthermore, there may be an increase in horizontal force capability in the non-injured leg as a possible compensatory adaptation to the hamstring injury. Given the high incidence of hamstring injuries and the strength and conditioning coach's role in rehabilitation of injury and improvement of performance, it would seem good practice to monitor and improve horizontal force capability in the hamstring injured athlete.